Wellbeing of Chilean older adults is associated with group participation - Palma Candia, Oskarina Carmen; Hueso-Montoro, César; Ortega-Valdivieso, Azucena; Montoya-Juárez, Rafael; Cruz-Quintana, Francisco (My University, 2016)
Background: Subjective aspects such as personal growth and the development of their potential are relevant for the perception of wellbeing of older adults. These dimensions appear to be connected with meaningful group participation. Aim: To assess the perception of psychological wellbeing of older adults in a Chilean region and determine its association with socio-demographic variables and participation in organizations. Material and Methods: Ryff's scale of psychological wellbeing perception was applied to 101 adults (43 men) from Magallanes, aged 60 and 88 years. Sociodemographic data was also collected. Results: Mean wellbeing scores reported were 193.7 ± 20 (maximum score: 234). Those older adults who participated in organizations had higher scores than those who did not take part in them. Participation in organizations appeared to be specifically associated to positive relationships (p = 0.03) and personal growth (p < 0.01). The number of organizations in which older adults participated was positively correlated with the perception of wellbeing (p < 0.01). Greater personal wellbeing was associated with leadership roles in organizations (p = 0.01). Significant differences between level of schooling and personal growth (p = 0.01) were also observed found. There were no differences associated with sex, age and marital status. Conclusions: The perception of wellbeing of older adults is influenced by their participation in organizations. Leadership is associated with the highest levels of wellbeing.
Factores sociodemográficos y de participación social relacionados con el bienestar psicológico en adultos mayores en la región de Magallanes, Chile
Keywords: aged; health promotion; occupations; social participation